An Internet-Based Physical Activity Intervention to Improve Quality of Life of Inactive Older Adults: A Randomized Controlled Trial - Broekhuizen, Karen; de Gelder, Jelle; Wijsman, Carolien A; Wijsman, Liselotte W; Westendorp, Rudi GJ; Verhagen, Evert; Slagboom, Pieternella E; de Craen, Anton J; van Mechelen, Willem; van Heemst, Diana; van der Ouderaa, Frans; Mooijaart, Simon P (JMIR Publications, 2016)
BackgroundIncreasing physical activity is a viable strategy for improving both the health and quality of life of older adults. ObjectiveThe aim of this study was to assess if an Internet-based intervention aimed to increase physical activity was effective in improving quality of life of inactive older adults. In addition, we analyzed the effect of the intervention on quality of life among those participants who successfully reached their individually targeted increase in daily physical activity as indicated by the intervention program, as well as the dose-response effect of increasing physical activity on quality of life. MethodsThe intervention was tested in a randomized controlled trial and was comprised of an Internet program-DirectLife (Philips)-aimed at increasing physical activity using monitoring and feedback by accelerometry and feedback by digital coaching (n=119). The control group received no intervention (n=116). Participants were inactive 60-70-year-olds and were recruited from the general population. Quality of life and physical activity were measured at baseline and after 3 months using the Research ANd Development 36-item health survey (RAND-36) and wrist-worn triaxial accelerometer, respectively. ResultsAfter 3 months, a significant improvement in quality of life was seen in the intervention group compared to the control group for RAND-36 subscales on emotional and mental health (2.52 vs -0.72, respectively; P=.03) and health change (8.99 vs 2.03, respectively; P=.01). A total of 50 of the 119 participants (42.0%) in the intervention group successfully reached their physical activity target and showed a significant improvement in quality of life compared to the control group for subscales on emotional and mental health (4.31 vs -0.72, respectively; P=.009) and health change (11.06 vs 2.03, respectively; P=.004). The dose-response analysis showed that there was a significant association between increase in minutes spent in moderate-to-vigorous physical activity (MVPA) and increase in quality of life. ConclusionsOur study shows that an Internet-based physical activity program was effective in improving quality of life in 60-70-year-olds after 3 months, particularly in participants that reached their individually targeted increase in daily physical activity. Trial RegistrationNederlands Trial Register: NTR 3045; http://www.trialregister.nl/trialreg/admin/rctview.asp?TC=3045 (Archived by WebCite at http://www.webcitation.org/6fobg2sjJ)